Praslavjanskoe *pepel"/ *popel" - Saenko, M. N. (Slovenski jezik, 2017)
The article examines geographical and historical relationships between descendants of the forms *popel" and *pepel" 'ashes' in the Slavic world and analyses four basic etymologies of this word (reduplicated derivative of *pel(H)- 'to burn', prefixed derivative of *pel(H)- 'to burn', derivative of *pelH- 'fine dust' and Nostratic etymology). 1
Keywords: etimologija; etymology; praslovanščina; Proto-Slavic; Slavic languages; slovanski jeziki